Process improvement of conventional palm oil milling: depulper - Azmi, Azlin Suhaida; Somasundaram, Mageswari; Jimat, Dzun Noraini (IIUM Press, 2011)
One of the objectives of this study was to analyze the capability and efficiency of depulper in separating loose fruits cooked at atmospheric pressure into fibrous mesh and nuts. This analysis leads to possibility in replacing the function of conventional digester with depulper. The study confirmed that depulper gave better separation of mixture of nuts and light fibers for the fruit bunches cooked at 1 bar compared to those cooked at 3 bars. However, the equipment gave almost similar separation of fibrous mesh at both pressures. Thus the study confirmed the proposed depulper can be integrated to the rest of the palm oil milling process in a conventional palm oil mill as well as integrating it in the proposed alternative palm oil milling process.